Frontispiece: Tuning Gas Adsorption by Metal Node Blocking in Photoresponsive Metal–Organic Frameworks. Issue 57 (12th October 2018) - Yang, Chi‐Ta; Kshirsagar, Aseem Rajan; Eddin, Azzam Charaf; Lin, Li‐Chiang; Poloni, Roberta
Abstract : The reversible decrease in CO2 adsorption measured experimentally upon light irradiation in a photoresponsive metal‐organic framework (MOF), PCN‐123, is identified to be primarily attributed to the blocking of the strong adsorbing metal sites by azobenzene molecules upon isomerization to cis configuration. This study, performed by combining first?principles calculations and classical molecular simulations, further shows that the same mechanism can be applied to another MOF as well as to other molecules such as alkanes and toxic gases. This suggests the general applicability of this identified key mechanism. For more information see the Communication by L.‐C. Lin and R. Poloni on page 15167 ff.